Editorial – The Torture Journal: A home for all - Pérez-Sales, Pau (Torture Journal, 2018)
The presence and work of the previous Editor in Chief, Lilla Hárdi, lives on in this issue which is largely a reflection of her work. With respect to the future, the members of the editorial team and the Editorial Advisory Board look forward to sharing some of the key ideas for the next steps in the history of the journal in the next issue. We can also look forward to the IRCT’s Scientific Symposium in Mexico in December with its more than 200 presentations. This is a unique opportunity to get a global picture of the field at this time, as well as reviewing past achievements and ways forward. Lastly and importantly, we wish to express again that we welcome and look forward to your contributions; the Torture Journal must strive to be a home for all.